Effect of isolated lactic acid bacteria on the quality and bacterial diversity of native grass silage - Bao, Jian; Ge, Gentu; Wang, Zhijun; Xiao, Yanzi; Zhao, Muqier; Sun, Lin; Wang, Yu; Zhang, Jiawei; Jia, Yushan; Du, Shuai (Frontiers in Plant Science, 2023)
The objective of this study was to isolate lactic acid bacteria (LAB) from native grasses and naturally fermented silages, determine their identity, and assess their effects on silage quality and bacterial communities of the native grasses of three steppe types fermented for 60 d. Among the 58 isolated LAB strains, Limosilactobacillus fermentum (BL1) and Latilactobacillus graminis (BL5) were identified using 16S rRNA sequences. Both strains showed normal growth at 15–45°C temperature, 3–6.5% NaCl concentration, and pH 4–9. Two isolated LAB strains (labeled L1 and L5) and two commercial additives (Lactiplantibacillus plantarum and Lentilactobacillus buchneri; designated as LP and LB, respectively) were added to native grasses of three steppe types (meadow steppe, MS; typical steppe, TS; desert steppe, DS), and measured after 60 d of fermentation. The fresh material (FM) of different steppe types was treated with LAB (1 × 105 colony forming units/g fresh weight) or distilled water (control treatment [CK]). Compared with CK, the LAB treatment showed favorable effects on all three steppe types, i.e., reduced pH and increased water-soluble carbohydrate content, by modulating the microbiota. The composition of bacterial community in native grass silage shifted from Pantoea agglomerans and Rosenbergiella nectarea to Lentilactobacillus buchneri at the species level. The abundance of Lentilactobacillus buchneri and Lactiplantibacillus plantarum increased significantly in L1, L5, LP, and LB treatments, respectively, compared with CK (p < 0.05). In summary, the addition of LAB led to the reconstruction of microbiota and modified the quality of silage, and L. fermentum and L. graminis improved the performance of native grass silage.